2016
DOI: 10.1021/acs.inorgchem.6b00218
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Heavy Cyclodipnictadiphosphanes [ClE(μ-P-Ter)]2 [E = P, As, Sb, or Bi; Ter = 2,6-bis(2,4,6-trimethylphenyl)phenyl]

Abstract: A complete series of terphenyl-substituted 1,3-dichloro-1,3-dipnicta-2,4-diphosphanes {[ClE(μ-P-Ter)]2, where E = P, As, Sb, or Bi and Ter = 2,6-bis(2,4,6-trimethylphenyl)phenyl} was prepared and fully characterized. While the heavy derivatives with E = Sb or Bi can be accessed via conversion of silylated phosphanes with amino-dichloropnictanes and subsequent elimination of TerNH2, the lighter congeners could be prepared only by a metathesis reaction of [ClBi(μ-P-Ter)]2 with PCl3 and AsCl3. Spectroscopic and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Recently, we prepared the four‐membered heterocycles [ClE(μ‐PTer)] 2 containing the heavy pnictogens E=P, As, Sb, Bi . It is known that the supermesityl (Mes*) substituent stabilize the monomeric species better than the dimer in heterocycles such as [ClE(μ‐NTer)] 2 compared to the terphenyl substituent .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we prepared the four‐membered heterocycles [ClE(μ‐PTer)] 2 containing the heavy pnictogens E=P, As, Sb, Bi . It is known that the supermesityl (Mes*) substituent stabilize the monomeric species better than the dimer in heterocycles such as [ClE(μ‐NTer)] 2 compared to the terphenyl substituent .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the resonance of 2 is a broad singlet at +5.4 ppm (Δ ν 1/2 =99 Hz; cf. TerPAsCl+1.8 ppm) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…compounds of the type [XP(m-NR)] 2 (A,X = halogen, R = sterically demanding group; Scheme 1) were shown to be easilyf unctionalized by halide abstraction, substitution reactions, or reduction, rendering them worthwhile building blocks in phosphorus-nitrogen chemistry (Scheme 2). [21][22][23][24][25][26] More recently,w eb ecamei nterested in the reactivity of cyclic phosphaneso ft he type [XP(m-PR)] 2 (C), [27][28][29][30][31] which had barelyb een investigated prior to our work. In particular,w e were interested in how the reaction behaviour of these species wouldc omparet ot he congeneric N 2 P 2 ring systems (A), in view of the formal replacement of the two Na toms by phosphorus.I tw as found that the P 4 ring system C displayed at endencyt os tabilizep ositive charges (induced by halide abstraction or substitution)b yr earrangement reactions associated with the formation of transannular PÀPb onds (Scheme 3).…”
Section: Introductionmentioning
confidence: 99%